Impact of distance and vertical placement of distal implants on bone mechanics in bar-retained overdenture treatment: A 3D finite element study - Danesh Ghahramanimarangalou; Nurullah Türker; Cennet Neslihan Eroğlu (PLoS ONE, 2025)
Objective In bar-retained, four-implant supported overdentures, implant positioning influences load transfer to the bone. Variations in distance and vertical alignment between implants may alter stress and strain distribution, affecting long-term outcomes. This study evaluates how the distance and vertical position of the distal implant relative to its neighboring implant affect stress and strain in the surrounding bone using 3D finite element analysis. Materials and methods Four groups were formed by shifting the neighboring implant mesially at 1 mm intervals, creating inter-implant distances of 3.8, 4.7, 5.6, and 6.5 mm. Each group included seven subgroups, where the distal implant was vertically positioned 1, 2, or 3 mm coronally or apically relative to its neighbor. A vertical load of 100 N was applied to the bar’s cantilever. Von Mises stress, maximum and minimum principal stresses, and strain values were calculated for 28 models. Results Maximum compressive stress and strain were observed at the distal aspect of the cortical bone surrounding the distal implant, averaging -49 Mpa (megapascal) and 3100 µε (microstrains), respectively. Apical positioning of the distal implant reduced compressive stress and strain by up to 22%, whereas coronal positioning produced similar or slightly lower compressive values but increased tensile stress and strain in the mesial cortical bone around the neighboring implant (maximum 25.7 MPa and 1578 µε). Increasing the interimplant distance consistently elevated both stress and strain in the surrounding bone. Conclusion Within the limitations of finite element analysis, minor vertical deviations in distal implant positioning due to bone irregularities or defects do not substantially increase cortical bone stress or strain. However, greater horizontal spacing between implants may result in higher biomechanical loads, emphasizing the importance of careful implant positioning for long-term success.